RDA : Resource Description & Access - Joint Steering Committee for Development of RDA; American Library Association; Library Association of Australia. Cataloguing Committee; British Library; Canadian Committee on Cataloguing; Library of Congress; Canadian Library Association; Chartered Institute of Library and Information Professionals (Great Britain); Deutsche Nationalbibliothek (Chicago, IL : American Library Association ; Ottawa, ON : Canadian Library Association ; London : CILIP: Chartered Institute of Library and Information Professionals, 2015)
Full text print version of RDA offers a snapshot that serves as an offline access point to RDA. Contains the content of RDA pulled from the RDA Toolkit database.
Recording attributes of manifestation and item -- Recording attribute of work and expression -- Recording attributes of person, family, and corporate body -- Recording attributes of concept, object, event, and place -- Recording primary relationships between work, expression, manifestation, and item -- Recording relationships to persons, families, and corporate bodies -- Recording relationships to concepts, objects, events, and places -- Recording relationships between works, expressions, manifestations, and items -- Recording relationships between persons, families, and corporate bodies -- Recording relationships between concepts, objects, events, and places.
'Includes changes and updates through April 2015.'
Includes bibliographical references and indexes.
Includes index.
Also available online as part of the RDA toolkit.
Text in English.
'Representing the American Library Association, the Australian Committee on Cataloguing, the British Library, the Canadian Committee on Cataloguing, CILIP: Chartered Institute of Library and Information Professionals, Deutsche Nationalbibliothek, the Library of Congress.'
Keywords: Resource description & access; Descriptive cataloging -- Standards